2006
DOI: 10.2131/jts.31.265
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP BETWEEN AUC of 5'-DFUR AND TOXICITY OF CAPECITABINE, FLUOROPYRIMIDINE CARBAMATE ANALOGS, AND 5'-DFUR IN MONKEYS, MICE, AND RATS

Abstract: -Capecitabine is an oral fluoropyrimidine carbamate which is converted to 5-fluorouracil (5-FU) via 3 enzymatic step to 5'-deoxy-5-fluorocytidine (5'-DFCR), 5'-deoxy-5-fluorouridine (5'-DFUR), and finally 5-FU. We performed 4-week toxicity studies of capecitabine (N 4 -pentyloxycarbonyl-5'-deoxy-5-fluorouridine), galocitabine (trimethoxybenzyl-5'-deoxy-5-fluorocytidine), 4 different fluoropyrimidine carbamate analogs (R=butyl, isopentyl, propyl, or phenethyl), and 5'-DFUR in cynomolgus monkeys with toxicokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…The histopathological changes of small and large intestines treated with capecitabine in mice at 1.1 and 2.2 mmol/kg/day and monkeys at 0.5 and 1.0 mmol/kg/ day for 4 weeks and the toxicokinetics are summarized in Table 4 (data are from Shindoh et al, 2006). The systemic exposure of 5'-DFUR AUC was almost the same at 2.2 mmol/kg in mice and 0.5 mmol/kg in monkeys.…”
Section: Comparison Of Intestinal Toxicity and Systemic Exposure In Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The histopathological changes of small and large intestines treated with capecitabine in mice at 1.1 and 2.2 mmol/kg/day and monkeys at 0.5 and 1.0 mmol/kg/ day for 4 weeks and the toxicokinetics are summarized in Table 4 (data are from Shindoh et al, 2006). The systemic exposure of 5'-DFUR AUC was almost the same at 2.2 mmol/kg in mice and 0.5 mmol/kg in monkeys.…”
Section: Comparison Of Intestinal Toxicity and Systemic Exposure In Mmentioning
confidence: 99%
“…In the case of capecitabine, as it likely passes through the intestinal mucosa as an intact molecule, production of 5-FU in intestinal mucosa is thought to be lower than with 5'-DFUR and therefore may induce lower toxicity in the intestine. We have reported that the toxicity of capecitabine in monkeys was reduced compared with that of 5'-DFUR based on mmol/kg dose and AUC of 5'-DFUR (Shindoh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A significantly higher DFUR AUC was found in females; however, this did not lead to a difference in circulating 5FU. One study reported a correlation between DFUR AUC with toxicities in animals, but these findings were not affirmed in humans (Shindoh et al , 2006). …”
Section: Discussionmentioning
confidence: 99%
“…The repetitive oral administration of capecitabine plus oxaliplatin (XELOX) regimen is a standard treatment for CRC similar to the FOLFOX and FOLFIRI regimens (Watanabe et al, 2015). Capecitabine is sequentially converted to 5-FU via a three-step enzyme activation process in the liver and tissues (Desmoulin, Gilard, Malet-Martino, & Martino, 2002;Shindoh et al, 2006;Shindoh, Nakano, Yoshida, & Ishigai, 2011). First, capecitabine is converted to 5′deoxy-5-fluorocytidine (5′-DFCR) by carboxylesterase (CES), mainly in the liver.…”
Section: Introductionmentioning
confidence: 99%